Pioglitazone for secondary prevention after ischemic stroke and transient ischemic attack: rationale and design of the Insulin Resistance Intervention after Stroke Trial - Viscoli, Catherine M.; Ringleb, Peter A. (American heart journal, 2014)
Background - Recurrent vascular events remain a major source of morbidity and mortality after stroke or transient ischemic attack (TIA). The IRIS Trial is evaluating an approach to secondary prevention based on the established association between insulin resistance and increased risk for ischemic vascular events. Specifically, IRIS will test the effectiveness of pioglitazone, an insulin-sensitizing drug of the thiazolidinedione class, for reducing the risk for stroke and myocardial infarction (MI) among insulin resistant, nondiabetic patients with a recent ischemic stroke or TIA. - Design - Eligible patients for IRIS must have had insulin resistance defined by a Homeostasis Model Assessment-Insulin Resistance >3.0 without meeting criteria for diabetes. Within 6 months of the index stroke or TIA, patients were randomly assigned to pioglitazone (titrated from 15 to 45 mg/d) or matching placebo and followed for up to 5 years. The primary outcome is time to stroke or MI. Secondary outcomes include time to stroke alone, acute coronary syndrome, diabetes, cognitive decline, and all-cause mortality. Enrollment of 3,876 participants from 179 sites in 7 countries was completed in January 2013. Participant follow-up will continue until July 2015. - Summary - The IRIS Trial will determine whether treatment with pioglitazone improves cardiovascular outcomes of nondiabetic, insulin-resistant patients with stroke or TIA. Results are expected in early 2016.